(untitled) (Cultura Económica, 2019)
After a brief tour through the milestones in the theoretical development of the subject, the economist Orlando Ferreres examines the process of economic growth in our country through a comparison between the two centuries of our nation’s history. The clear decline that occurred in the second period leads to the problem of investment and institutions, two issues closely linked in economic policy. The loss of the institutional dimension appears as the most important obstacle for a long-term growth. Finally, the author points out the importance of the teachings of some new currents of thought, especially those that analyze the relationship between politics and economics.